Explosive blast damage resistance of three-dimensional textile composites. (September 2017) - Kerber, A.; Gargano, A.; Pingkarawat, K.; Mouritz, A.P.
Abstract: The damage resistance of 3D textile composites when subjected to shock wave loading caused by an explosive blast is experimentally investigated. Non-crimp 3D orthogonal textile carbon-epoxy composites with different volume contents of through-thickness z-binder yarns are subjected to explosive blasts of increasing intensity, and the resultant damage is compared to a 2D woven carbon-epoxy laminate. At high blast impulse, the 3D textile composites are highly effective at resisting large delamination crack growth, and display superior damage resistance compared to the 2D laminate. The delamination resistance of the 3D textile composites at high blast impulse increases with their z-binder yarn content, and this correlates with higher modes I and II interlaminar fracture toughness properties. Furthermore, the 2D laminate completely shatters under high blast impulse whereas the 3D textile composites remain intact, which is also evidence of higher explosive damage resistance.